SOCIAL MEDIA RELATIONSHIP RELATED TO COVID-19 PANDEMI INFORMATION WITH HOUSEWIDE ANXIETY LEVEL IN 2020 - 2021 PERUM SUTRI RT 06/ RW 03 SOBO, BANYUWANGI - Harwanti Noviandari; Tiara Ayu; Miftahul Arifin (International Jurnal of Education Schoolars, 2022)
Currently there is an outbreak of Corona Virus Disease (Covid-19) with symptoms of acute respiratory disorders such as rapid fever, which creates a perception for readers, one of which is housewives. The perception or understanding that housewives have about Covid-19 invites excessive anxiety so that it has a very psychological impact. The purpose of this study was to describe the relationship between social media related to the Covid-19 pandemic information and the level of anxiety of housewives in 2020-2021 at Perum Sutri RT 06 / RW 03 Sobo Banyuwangi. This study was conducted to determine whether there is a relationship between information on the Covid-19 pandemic on social media and the anxiety of housewives during the Covid-19 pandemic. This research is a type of descriptive quantitative research, data collection is done by using observation techniques, distributing questionnaires and documentation. Respondents in this study were housewives of Perum Sutri Sobo RT 06/ RW 03 Sobo Banyuwangi who experienced the impact of the Covid-19 pandemic. The number of respondents studied were 44 respondents with an age range of 30 to 45 years. The results of this study indicate that the relationship obtained is positive between social media and anxiety. The correlation coefficient level (rxy) generated from the two variables is (rxy) = 0.055 with a significance level of P = 0.724 (P > 0.05). So that it shows that the higher the use of social media by housewives, the level of anxiety will be high.